Molecular characterization of Msp2/P44 of Anaplasma phagocytophilum isolated from infected patients and Haemaphysalis longicornis in Laizhou Bay, Shandong Province, China. - Yong Wang; Chuangfu Chen; Lijuan Zhang (PLoS ONE, 2013)
Molecular characterization of the MSP2/P44 protein of Anaplasma phagocytophilum may determine not only if the bacterium is capable of invading hosts but also whether it generates antigenic variation for the purpose of escaping the host immune response, resulting in various pathologic injuries and serious clinical outcomes. Chinese anaplasmosis patients usually present with serious manifestations, and the fatality rate is as high as 26.5%. In this study, we amplified, cloned and sequenced the msp2/p44 genes of three Chinese A. phagocytophilum isolates from Laizhou Bay, Shandong Province, where human granulocytic anaplasmosis (HGA) patients present severe clinical manifestations, and analyzed their genetic characterization and structural features. We also compared them with the HZ and Webster A. phagocytophilum strains. The sequences for both strains are available in GenBank. Analyses indicated that Chinese A. phagocytophilum isolates were significantly different from the HZ and Webster strains in terms of nucleotide sequences, amino acid sequences and protein secondary and tertiary structures. Moreover, the number of immunologic B-cell epitopes (19) of the MSP2 protein of the Chinese isolates was higher than that of the A. phagocytophilum strains HZ (16) and Webster (9). This genetic diversity of the MSP2/P44 protein of Chinese A. phagocytophilum isolates might be relevant and might have serious clinical outcomes. This observation could provide a clue to further understand the pathogenesis of Chinese A. phagocytophilum.